Loading PCM Into Buildings Envelope to Decrease Heat Gain-Performing Transient Thermal Analysis on Nanofluid Filled Solar System - Amirahmad, Aslam; Maglad, Ahmed Mustafa; Mustafa, Jawed; Cheraghian, Goshtasp (Frontiers in Energy Research, 2021)
The high share of buildings in energy consumption and carbon dioxide emission has led researchers to seek techniques to reduce energy consumption in this sector. In this study, considering a hot and arid climate region, the wall’s heat gain was investigated. To reduce energy demand, three techniques of adding PCM, combining absorption chiller with a solar system and dispersing nanoparticles were used and the results were evaluated transiently. In July, the addition of PCM to the building's walls reduced the heat exchange between interior and exterior spaces up to 21%. To cool the interior spaces, the combination of absorption chiller + fan coil was used and several flat plate collectors were integrated with it to reduce energy demand. By collecting energy in solar collectors and using a stratified tank, energy consumption in the generator section was reduced by 450 kWh. Nanoparticles were used to improve the solar system performance and it was found that loading ZnO and Al2O3 nanoparticles is useful. Dispersing ZnO into water increased the energy-saving by 9.5% while the second nanoparticle improved it by 14.5%.